Targeting tubulointerstitial remodeling in proteinuric nephropathy in rats - Yazdani, Saleh (Dis Model Mech, 2015)
Proteinuria is an important cause of tubulointerstitial damage. Anti-proteinuric interventions are not always successful, and residual proteinuria often leads to renal failure. This indicates the need for additional treatment modalities by targeting the harmful downstream consequences of proteinuria. We previously showed that proteinuria triggers renal lymphangiogenesis before the onset of interstitial inflammation and fibrosis. However, the interrelationship of these interstitial events in proteinuria is not yet clear. To this end, we specifically blocked lymphangiogenesis (anti-VEGFR3 antibody), monocyte/macrophage influx (clodronate liposomes) or lymphocyte and myofibroblast influx (S1P agonist FTY720) separately in a rat model to investigate the role and the possible interaction of each of these phenomena in tubulointerstitial remodeling in proteinuric nephropathy. Proteinuria was induced in 3-month old male Wistar rats by adriamycin injection. After 6 weeks, when proteinuria has developed, rats were treated for another 6 weeks by anti-VEGFR3 antibody, clodronate liposomes or FTY720 up to week 12. In proteinuric rats, lymphangiogenesis, influx of macrophages, T cells and myofibroblasts, and collagen III deposition and interstitial fibrosis significantly increased at week 12 vs week 6. Anti-VEGFR3 antibody prevented lymphangiogenesis in proteinuric rats, however, without significant effects on inflammatory and fibrotic markers or proteinuria. Clodronate liposomes inhibited macrophage influx and partly reduced myofibroblast expression; however, neither significantly prevented the development of lymphangiogenesis, nor fibrotic markers and proteinuria. FTY720 prevented myofibroblast accumulation, T-cell influx and interstitial fibrosis, and partially reduced macrophage number and proteinuria; however, it did not significantly influence lymphangiogenesis and collagen III deposition. This study showed that proteinuria-induced interstitial fibrosis cannot be halted by blocking lymphangiogenesis or the influx of macrophages. On the other hand, FTY720 treatment did prevent T-cell influx, myofibroblast accumulation and interstitial fibrosis, but not renal lymphangiogenesis and proteinuria. We conclude that tubulointerstitial fibrosis and inflammation are separate from lymphangiogenesis, at least under proteinuric conditions.